PENGARUH LATIHAN TEMBAKAN KE GAWANG “SWERVING” TERHADAP KEMAMPUAN SHOOTING PADA TIM SEPAK BOLA MTs NEGERI KOTA DUMAI - Fajrul Rozi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted to determine whether there are effects of exercise shot to goalkeeper "Swerving" Against ability Shooting At Team Soccer MTs Dumai City, so that at the time of attack patterns players are able to create more goals into the opponent's goal and can to win the game.The problem in this research that the ability of the athlete shooting MTs Dumai City team is still lacking, it is seen from the various trials and friendly matches or official and this is one of the causes of the defeat. This type of research is a kind of research experiments to see the effects of this form of exercise. The purpose of this study is to look at the effects of exercise shots on goal (Swerving) on the ability of shooting at a football team MTs Dumai cityThe population in this study is the team MTs Dumai City totaling 16 people. A sampling technique that by using total sampling, where the total population sampled. Data collection techniques derived from the pre-test and post test. Instrument in this study using Test Shooting / Kicking the ball to Goal (Shooting) as a tool to measure the accuracy of shooting. Based on the analysis of statistical data, generate Preetest Lhitung amount 0,1621, and data Posttest Lhitung amount 0,1797, and Lhitung < Ltabel. Then the data is normally distributed. Analyses were performed using t-test. based on data analysis and discussion, as evidenced by Thitung amounted to 6,9 and 1,764 Ttabel. Means Thitung>Ttabel. At some level ɑ = 0.05. It can be concluded that there is significant influence of practice shots on goal against the shooting ability on the football team MTs Dumai City.Keywords: Shots on Goal (Swerving), Shooting Ability, Football.